Microcystic meningioma mimicking pleomorphic xanthoastrocytoma - Banstola, S; Pathak, T; Neupane, S; Shrestha, S; Basyal, R; Pun, CB; Lee, MC (Journal of Pathology of Nepal, 2011)
Microcystic meningioma is a distinct morphological variant of meningioma, characterized by loose texture and microcysts with formation of large extracellular spaces containing edematous fluid. The tumor cells have stellate and vacuolated cytoplasm with long cytoplasmic processes. We report a case of microcystic meningioma occurring in a 60 year-old man. Histological features showed tumor cells with abundant foamy cytoplasm, pleomorphic nucleus with vesicular chromatin and prominent nucleoli which mimicked pleomorphic xanthoastrocytoma. The clinical presentation and histopathological diagnostic dilemma along with immunohistochemistry is discussed. Keywords: MicrocysticMeningioma; Pleomorphic xanthoastrocytoma Immunohistochemistry DOI: http://dx.doi.org/10.3126/jpn.v1i2.5413 JPN 2011; 1(2): 158-160